Atractylenolide III Relieves Diphenoxylate-Induced Constipation via Gut Microbiota and Bile Acid Pathway Modulation - Chen, Simin; Zhang, Zhibin; Pang, Jun; Guan, Lina; Wu, Qingfeng; Wang, Qiuxiao; Li, Qian; Tang, Xuegui (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: An imbalance of intestinal flora and its fermentation products can disrupt intestinal peristalsis and lead to constipation. This study aimed to investigate how Atractylenolide III (ATL-III) may enhance constipation treatment by regulating the gut microbiota-bile acid metabolism pathway. Materials and Methods: In this study, an experimental mouse model of constipation was established and intestinal motility, colonic neurotransmitter release, and bile acid metabolism were measured. By 16S rDNA gene sequencing, the character of the balance of gut microbiota was observed in constipated mice, and the relationship between intestinal flora, bile acid, and neurotransmitter secretion was analyzed. Results: Our findings proved that ATL-III treatment profoundly boosted intestinal motility, promoted colonic neurotransmitter release, and prevented gut barrier damage in constipated mice induced by diphenoxylate. Liquid chromatography-tandem mass spectrometry showed that ATL-III also regulated bile acid metabolism in constipated mice. Several intestinal bacteria at phylum, family, and genus levels were statistically reversed when atractylenolide III was administered to constipated mice, as revealed by 16S rDNA gene sequencing. This partly led to a balance in the production of intestinal metabolites, including bile acids. ATL-III-initiated constipation prevention confirms the importance of gut microbiota. Conclusion: ATL-III may ameliorate the development of compound diphenoxylate-induced constipation in mice by remodeling the structure of the gut microbial community.
Keywords: Atractylenolide III (ATL-III); Constipation; Intestinal barrier; Gut microbiota; Bile acids (BAs).